Strengthening Religious Moderation in the Digital Space Through Creative Works - Kusumaningrum, Demeiati Nur (Universitas Muhammadiyah Yogyakarta, 2025)
This paper examines the role of Islamic organizations in promoting religious moderation in the digital era, focusing on Indonesia, the largest Muslim-populated country in Asia. The study highlights the importance of digital transformation policies in providing inclusive spaces for balanced and democratic information dissemination. It emphasizes the need for maintaining harmony between Muslims and non-Muslims, particularly in the face of terrorism and Islamophobia. The research employs a qualitative methodology, utilizing document and content analysis to explore how Islamic organizations use digital platforms to counter violent narratives and promote a positive image of Islam. The findings suggest that optimizing digital da'wah through influencers, developing views of religious moderation, and utilizing creative works can effectively engage the younger generation and address misconceptions about Islam. The study underscores the importance of ethical and creative use of social media, collaboration with content creators, and the establishment of online communities to promote positive content and reduce social tensions. This approach contributes to a more harmonious and inclusive global society by fostering better understanding between the Western and Islamic world.